(untitled) (International journal of artificial intelligence, 2026)
This article looks at Sh. Turdiev’s research on European literature in Uzbekistan, translation studies, and literary connections between cultures. It discusses how he studied Uzbek translations of major Western writers like Shakespeare, Heine, Pushkin, Gogol, Turgenev, Chekhov, and Gorky, and how these translations helped shape modern Uzbek literature and its aesthetic development. A significant part of Turdiev’s work highlights early Uzbek translators and intellectuals, especially Cho‘lpon and his contemporaries. They played a crucial role in bringing world literature into the Uzbek cultural space, not just by translating texts, but by adapting them in a way that made them meaningful for local readers and writers. The article also touches on Turdiev’s research on Pushkin in Uzbekistan. He explores Pushkin’s style, philosophical ideas, and possible Eastern influences in his writing. In his comparative study “Mushtaraklik,” Turdiev points out interesting similarities between Pushkin’s stories and Central Asian folk tales, suggesting that different literary traditions may share common roots and themes. In addition, the study covers Uzbekistan’s cultural and academic relations in the 1920s–1930s, showing how educational exchanges with Europe and the efforts of Jadid thinkers helped build intellectual bridges across countries. It also looks at how foreign writers portrayed Uzbekistan, often with admiration for its culture, history, and artistic richness. Overall, Turdiev’s work is presented as an important bridge between Uzbek and world literature, contributing to comparative literary studies and helping us better understand how Uzbekistan became part of broader global cultural conversations.